Polarization of Human Macrophages by Interleukin-4 Does Not Require ATP-Citrate Lyase - Namgaladze, Dmitry; Zukunft, Sven; Schnütgen, Frank; Kurrle, Nina; Fleming, Ingrid; Fuhrmann, Dominik; Brüne, Bernhard (Frontiers in Immunology, 2018)
Macrophages exposed to the Th2 cytokines interleukin (IL) IL-4 and IL-13 exhibit a distinct transcriptional response, commonly referred to as M2 polarization. Recently, IL-4-induced polarization of murine bone marrow-derived macrophages has been linked to acetyl-CoA levels through the activity of the cytosolic acetyl-CoA-generating enzyme ATP-citrate lyase (ACLY). Here, we studied how ACLY regulated IL-4-stimulated gene expression in human primary macrophages. Although multiple ACLY inhibitors attenuated IL-4-induced target gene expression, this effect could not be recapitulated by silencing ACLY expression. Furthermore, ACLY inhibition failed to alter cellular acetyl-CoA levels and histone acetylation. We generated ACLY knockout human THP-1 macrophages using CRISPR/Cas9 technology. While these cells exhibited reduced histone acetylation levels, IL-4-induced gene expression remained intact. Strikingly, ACLY inhibitors still suppressed induction of target genes by IL-4 in ACLY knockout cells, suggesting off-target effects of these drugs. Our findings suggest that ACLY may not be the major regulator of nucleocytoplasmic acetyl-CoA and IL-4-induced polarization in human macrophages. Furthermore, caution should be warranted in interpreting the impact of pharmacological inhibition of ACLY on gene expression